Governance of sports companies with shares is a binding law or guide From the point of view of the members of the Board of Sports Clubs - Oucif, nor el houda; bennour, Mamar (sports creativity, 2025)
The study aimed at evaluating the governance of sports companies through the views of the members of the board of directors of some professional clubs by providing a comprehensive concept of the governance of sports companies with a statement of their importance in terms of a binding law and guide, and for that a questionnaire was designed to measure the directions of the board members of the two clubs Star Young people Magra and Olympic chelf, it was concluded that most of the sample members of the study consider the governance of sports companies to be a binding law.